Barriers to Implementation of Rapid and Point-of-Care Tests for Human Immunodeficiency Virus Infection. Issue 3 (September 2015) - Pai, Nitika Pant; Wilkinson, Samantha; Deli-Houssein, Roni; Vijh, Rohit; Vadnais, Caroline; Behlim, Tarannum; Steben, Marc; Engel, Nora; Wong, Tom
<x xml:space="preserve">Abstract</x> Background Implementation of human immunodeficiency virus rapid and point-of-care tests (RDT/POCT) is understood to be impeded by many different factors that operate at 4 main levels—test devices, patients, providers, and health systems—yet a knowledge gap exists of how they act and interact to impede implementation. To fill this gap, and with a view to improving the quality of implementation, we conducted a systematic review. Methods Five databases were searched, 16, 672 citations were retrieved, and data were abstracted on 132 studies by 2 reviewers. Findings Across 3 levels (ie, patients, providers, and health systems), a majority (59%, 112/190) of the 190 barriers were related to the integration of RDT/POCT, followed by test-device–related concern (ie, accuracy) at 41% (78/190). At the patient level, a lack of awareness about tests (15/54, 28%) and time taken to test (12/54, 22%) dominated. At the provider and health system levels, integration of RDT/POCT in clinical workflows (7/24, 29%) and within hospitals (21/34, 62%) prevailed. Accuracy (57/78, 73%) was dominant only at the device level. Interpretation Integration barriers dominated the findings followed by test accuracy. Although accuracy has improved during the years, an ideal implementation could be achieved by improving the integration of RDT/POCT within clinics, hospitals, and health systems, with clear protocols, training on quality assurance and control, clear communication, and linkage plans to improve health outcomes of patients. This finding is pertinent for a future envisioned implementation and global scale-up of RDT/POCT-based initiatives.